Organizational factors, health outcomes, and their predictors in type 2 diabetes care in the occupied Palestine / Rami Salem Abdelmajid Mosleh - Rami Salem Abdelmajid Mosleh (Institute of Graduate Studies, UiTM, 2018)
Political instability of Palestine influenced economic, social, and health aspects. Diabetes prevalence at Palestine was 10%, with rising fund crisis and diabetes care problems. There was a limited research concerning diabetes care dimensions (organizational factors and health outcomes) and their predictors. Health outcomes included costs, diabetes self–care management, and glycaemic control. This study described patient characteristics, assessed organizational factors, diabetes self–care management, glycaemic control, and their predictors, evaluated drug utilization pattern, assessed costs and their predictors. This study had two phases, and was carried out at the National Centre for Chronic Diseases and Dermatology, Ramallah, Palestine. Phase one is retrospective cross–sectional in 330 participants recruited by convenience sampling method from a type 2 diabetes patients list who were seen regularly during the past one year. Phase two is an–observational follow–up that involved 79 participants selected from phase one participants by simple random sampling; they were followed–up for six months. Data on patient characteristics, organizational factors, diabetes self–care management, and glycaemic control were collected from personal interview and medical records review for both phases. Data on costs was obtained in phase two from personal interview in each visit. Good glycaemic control was defined as HbA1c ≤7%. Data was analyzed by SPSS v 16.0. Phase one showed that 51.2% were males, mean ± standard deviation age was 60±9.7 years, 88.5% had additional chronic diseases, and 46.1% were obese. The mean total overall organizational factors score was higher than average score (cumulative percentage=55.4%)…